PEOPLES PARTICIPATION FOR IDENTIFICATION OF PROBLEM FOR WATERSHED DEVELOPMENT - Patel, Neelam; Rajput, T.B.S. (Journal of Soil and Water Conservation, 2022)
One of the important aspects of overall development Is that the masses identify their problems themselves and conic up with their perceptions about their priorities. Participatory Rural Appraisal (PRA) technique have remained a useful strategy that enables community people decide on and prioritise their community needs. Rithauri village, situated in Block Sihora, District Jabalpur, ALP. was selected to conduct the PRA to find out the top most problem which is mainly responsible for under development of the village. Rithauri village is a part of group of six villages (Rithauri, Algora, Ram Kiriya, Katra Khamariya, Simariya & Dangwa) that fall in the Berni watershed development project under the National Watershed Management Programme. To identify the top most problem of village Rithauri, the snow ball sampling technique was used. The information collected from the selected farmers during PRA was used to determine Rank Based Quotient (RBQ) and Average Yield Loss Percentage (AYLP). The Magnitude Value (MV) of different problems faced by the village community was calculated as the product of RBQ, AYLP and the area affected by corresponding problem. Problem of irrigation water shortage ultimately resulted to be the top most problem of the village with rank I followed by weeds problem (Rank II) and lack of adequate employment in agriculture (Rank-111).